Association of persistent respiratory symptoms with severity of COVID-19 (BIRDEM Medical Journal, 2023)
Background: Coronavirus disease 2019 (COVID-19) is a new and highly contagious respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Symptoms and disease severity of COVID-19 vary from asymptomatic to severe or fatal illness. A major complication of those who survived from COVID-19 is the development of lung disease leading to persistence of respiratory symptoms. The objective of the present study was to find out the association of persistence of respiratory symptoms with severity of COVID-19.Methods: This prospective observational study was carried out in the Department of Respiratory Medicine, Bangabandhu Sheikh Mujib Medical University, Dhaka during the period from July 2020 to December 2020. During follow-up around three months (90.62±2.21 days) after the onset of the first COVID-19 symptoms, 500 patients were taken as the study sample.Results: Total patients were 500 with 206 (41.2%) severe cases. Two-fifths of the study participants had persistent respiratory symptom at 3 months. Persistence of respiratory symptoms was associated with severity of COVID-19 (p =